PENERAPAN REWARD DAN PUNISHMENT UNTUK MENINGKATKAN KEDISIPLINAN SISWA DI SDN MARGOREJO VI SURABAYA - Inayati, Nurul; Natasya, Rizki Dwi; Mustaghfirah, Walidatul; Khotimah, , Siti Khorriyatul (Universitas Islam Lamongan, 2024)
The purpose of this study is to identify the forms of reward and punishment that are effectively used and the implications of both reward and punishment. The research method employed is qualitative, with the type of research being field research, and data collection techniques include observation, interviews, and documentation. The research sample consists of third-grade students at SDN Margorejo VI. SDN Margorejo VI has implemented a learning system that prioritizes the use of rewards to enhance motivation, achievement, and student discipline, while avoiding the implementation of punishment. The form of reward given emphasizes recognition and appreciation of the students' learning process, whereas the existing form of punishment aims to provide positive encouragement in solving problems, rather than just punishment. This policy has successfully created a structured learning environment, developed social and emotional skills, and improved students' discipline character through real-life experiences about the importance of the relationship between actions and their consequences.